2017
DOI: 10.7150/thno.17544
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Strategy using Multifunctional Nanoconjugates for Efficient Simultaneous Detection of Escherichia coli O157: H7 and Vibrio cholerae O1

Abstract: The rapid and accurate quantification of the pathogenic bacteria is extremely critical to decrease the bacterial infections in all areas related to health and safety. We have developed an electrochemical strategy for simultaneous ultrasensitive detection of E. coli O157:H7 and Vibrio cholerae O1. This approach was based on the specific immune recognition of different pathogenic bacteria by multifunctional nanoconjugates and subsequent signal amplification. By employing the proposed biosensor, the concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In recent years, molecularly imprinted polymers (MIPs) have been used as promising alternatives to natural receptors to developing new generation of chemical/biological sensors due to their superiorities such as high adsorption capacity, high specific recognition of target molecules, desirable physical and chemical stability, excellent reusability, low cost and easy preparation offers. Reproduced from [109] with permission from Ivyspring International Publisher (E. coli O157 : H7 and Vibrio colerae = 1). Electrochemical sensors, provide much lower cost, more field portability and are predominant device in the market [114].…”
Section: Molecularly Imprinted Electrochemical Sensormentioning
confidence: 99%
“…In recent years, molecularly imprinted polymers (MIPs) have been used as promising alternatives to natural receptors to developing new generation of chemical/biological sensors due to their superiorities such as high adsorption capacity, high specific recognition of target molecules, desirable physical and chemical stability, excellent reusability, low cost and easy preparation offers. Reproduced from [109] with permission from Ivyspring International Publisher (E. coli O157 : H7 and Vibrio colerae = 1). Electrochemical sensors, provide much lower cost, more field portability and are predominant device in the market [114].…”
Section: Molecularly Imprinted Electrochemical Sensormentioning
confidence: 99%
“…At this point, it is worth to mention that very recently the Lobo-Castañón’s research group has reported, for the first time, the use of on-surface helicase-dependent amplification at ITO surfaces to quantify electrochemically very small amounts of genomic DNA extracted from Salmonella [ 31 ]. Attractive electrochemical nucleic acid sensors have been reported so far for non-invasive bacterial infections detection coupled with PCR [ 32 , 33 , 34 ], HDA [ 25 , 31 , 34 ], RPA [ 35 ] and HCR [ 36 ].…”
Section: Electrochemical Affinity Biosensing Of Infectious Pathogementioning
confidence: 99%
“…Electrochemical biosensors described to date for bacterial infections [ 28 , 32 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] comprise a rather limited number of immunosensors using antibodies able to detect the whole bacteria ( Streptococcus pseudopneumoniae , Escherichia coli and Vibrio cholerae ) [ 36 , 37 , 38 ] or specific surface bacterial proteins (PspA peptide) [ 28 ], and a wide variety of nucleic acid sensors targeting specific bacterial genes used along with different nucleic acid and signal amplification strategies [ 32 , 33 , 34 , 35 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Electrochemical Affinity Biosensing Of Infectious Pathogementioning
confidence: 99%
See 2 more Smart Citations